The Lost Hero: The Heroes of Olympus #1 #1 - Riordan, Rick (New York : Disney/Hyperion Books, 2010)
Jason, Piper, and Leo, three students from a school for "bad kids," find themselves at Camp Half-Blood, where they learn that they are demigods and begin a quest to free Hera, who has been imprisoned by Mother Earth herself.
Keywords: Mythology, Greek -- Juvenile fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; Greek mythology -- Fiction; Camps -- Fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; Monsters -- Fiction; Mythology, Greek -- Fiction; Camps -- Fiction; Monsters -- Fiction